Bibliometric Analysis with VOSviewer on Digital Transfor-mation Implications toward Social Enterprise in the Digital Era - Cici Anggraini; William Janaldo; Sudarmiatin; Trisetia Wijayanti (International Humanity Advance, Business & Sciences, 2026)
This paper explores how research on digital transformation and its connection to social enterprises has developed worldwide from 2020 to 2025. The study draws its data from the Scopus database and applies VOSviewer to map patterns of collaboration among authors, recurring keywords, and citation relationships. From 72 selected studies, a clear upward trend can be seen, with growing scholarly attention after 2022. The findings point to five key areas often discussed in this field: innovation and technology adoption, social entrepreneurship and value creation, sustainability and inclusion, changes in business models, and knowledge management. Over the years, the focus of discussion appears to have moved from basic digital readiness toward newer issues such as the role of artificial intelligence in social impact and the use of data to guide decisions. These shifts indicate that digital tools are increasingly central to how social enterprises operate and deliver value. By presenting an overview of existing work and identifying leading contributors, this research highlights where future collaboration and exploration might take place. The study also offers practical insights that could support policymakers and practitioners who aim to use technology to promote sustainable and inclusive growth.